2008
DOI: 10.3797/scipharm.0804-05
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Baicalin on Alveolar Bone Resorption in Rat Experimental Periodontitis

Abstract: Objective: In this study, the effects of baicalin -a flavonoid purified from Scutellaria baicalensis. Georgi, Scutellaria L. -on alveolar bone resorption in rat experimental periodontitis were examined. Method: 12 Sprague-Dawley rats (SD rats) were randomly divided into four groups: Group A1, A2, B and C. Except for Group C -the control group-, Group A1, A2 and B were used to establish the rat periodontitis model by repeat injection of Lipopolysaccharide (LPS). At the same time, Group A1 and A2 were injected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This action is associated with the presence of compounds: baicalin, baicalein, and wogonin. Baicalin in the rat model of periodontitis reduced alveolar bone loss and increased the surface fraction of collagen fibers by decreasing cyclooxygenase-2 and nitric oxide synthase proteins expression [ 19 , 20 ]. It promoted osteogenic activity in the human periodontal ligament and periodontal ligament cells by up-regulating the expression of osteoprotegerin (OPG) mRNA and proteins, down-regulating receptor activator of nuclear factor-κβ ligand (RANKL) mRNA and protein expression, and significantly reducing the ratio of RANKL/OPG expression [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This action is associated with the presence of compounds: baicalin, baicalein, and wogonin. Baicalin in the rat model of periodontitis reduced alveolar bone loss and increased the surface fraction of collagen fibers by decreasing cyclooxygenase-2 and nitric oxide synthase proteins expression [ 19 , 20 ]. It promoted osteogenic activity in the human periodontal ligament and periodontal ligament cells by up-regulating the expression of osteoprotegerin (OPG) mRNA and proteins, down-regulating receptor activator of nuclear factor-κβ ligand (RANKL) mRNA and protein expression, and significantly reducing the ratio of RANKL/OPG expression [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, SLPI inhibited alveolar bone resorption by LPS through lowered surface resorption of alveolar bone, narrowed trabecular bone space, raised trabecular bone number, and closed the trabecular bone to plate-like structure. Based on the analysis of micro-CT data, other studies have reported that baicalin inhibits alveolar bone resorption similarly to SLPI in LPS-injected rats (Chen et al 2008). In addition, simvastatin inhibits the expression of factors associated with osteoclastogenesis, and suppresses LPS-induced alveolar bone resorption in fat or lean rats (Jin et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…44 It was demonstrated that flavonoids may restore the alveolar therefore provide a bone mass by inhibiting LPS-induced bone resorption. 45,46 Therefore increased intake of flavonoids may proved to be beneficial prevention of periodontal disease.…”
Section: Flavonoidsmentioning
confidence: 99%